A olimpíada nacional em história do brasil (onhb) e o ensino médio integrado no ifrn - Costa Júnior, José Gerardo Bastos da (2017)
The National Olympiads of History of Brazil (NOHB) was created by Universidade Estadual de Campinas / SP (Unicamp) in 2009. It is a set of educational activities that aims to stimulate the knowledge and study of History of Brazil, in a playful and creative way. Thus, considering the great participation of the Federal Institutes of Education, Science and Technology in the NOHB editions, our aim in this research was to investigate whether this Olympiads can act as a facilitator in the development of integrative pedagogic practices in the Integrated High School, based on the Political-Pedagogical Project of IFRN. The methodological course of the investigation followed the following steps: readings with the purpose of building theoretical basis and analysis of the results of the study; exploratory research on the NOHB in its 2009 to 2017 editions; and analysis of the questions proposed by NOHB relating them to the guiding principles of the IFRN pedagogical practice. Regarding the theoretical basis, we initially used the main legal documents of Brazilian education, Law No. 9,394 / 96, which establishes the Guidelines and Bases of Brazilian Education (1996), National Curricular Guidelines (2001), National Curricular Guidelines (2006), the IFRN Political-Pedagogical Project (2012a) and the Work Proposal of the History Discipline in the Technical Courses of Integrated High School in the modalities Regular and EJA of IFRN (2012b). On Integrated High School and Professional and Technological Education, we based our research on Moura (2013, 2010, 2008, 2007), Frigotto; Ciavatta; Ramos (2012a), Ramos (2010), Kuenzer (2008; 2009), among others. With respect to NOHB, the studies of Meneguello (2011; 2015), Mariuzzo (2010), Miranda (2013; 2015) and Souza; Costa Junior (2016) were used as basis. As for History teaching, we had as support the studies of Bittencourt (2008; 2011) and Schimidt; Cainelli (2009). The research allowed us to conclude that, in the specific case of Integrated High School to Professional and Technological Education, we consider that NOHB collaborates in the training of student-citizen-workers and stimulates the pedagogical praxis of educators within the guiding principles of the PPP of IFRN, developing methodologies that emphasize research as a pedagogical principle, work as an educational principle, respect for diversity and the search for interdisciplinarity